PENYELESAIAN SENGKETA PERBANKAN BERKAITAN DENGAN PERLINDUNGAN KONSUMEN - Dian Herlambang; Muhammad Ridho Wijaya (Law Faculty of Universitas Bandar Lampung, 2020)
The economy is one aspect of human life that is vulnerable to offense and even evil in it. As the development of the electronic world and the turnover of global money increasingly fast, demanded that people connect with other parties that are banking institutions to manage the money he has. It can be utilized by the person who is not responsible for dredge profit by utilizing the weakness of the banking system both using conventional and electronic media use. The problem in this article is how the banking dispute resolution mechanism relates to consumer protection? The approach to the problem used is normative juridical with the literature study method. The results showed that the banking dispute resolution mechanism in relation to consumer protection can be through two banking dispute resolution mechanisms, namely internal dispute resolution and external dispute resolution of the dispute.